Abstracts Accepted for Publication 2017
DOI: 10.1136/annrheumdis-2017-eular.2231
|View full text |Cite
|
Sign up to set email alerts
|

AB0789 The psoriatic arthritis patient's journey: special emphasis on diagnosis and treatment delays

Abstract: BackgroundA delay in diagnosis and treatment of Psoriatic Arthritis (PsA) is associated with increased disability and damage in the long term. There is currently scarce data available about diagnosis delay, referrals delays, and time to first treatment in patients with PsA in developing countries.ObjectivesTo describe the journey of patients with psoriatic arthritis, with special emphasis on diagnosis and treatment delays.MethodsAll patients with PsA registered in the Rheumatology Unit data base (between 2000–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This is supported by a recent report for RA patients that highlighted that the mean duration from first disease symptom to rheumatologist consultation was 9.2 months, while the mean time to RA diagnosis was 14.2 months [33]. A similar study found that a delay in PsA diagnosis was greater than one year in nearly half of the patients [34]. The majority of patients with RA received treatment prescribed by a rheumatologist but treatment initiation was also found to be delayed (mean duration from first disease symptom of 16.9 months) [33].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This is supported by a recent report for RA patients that highlighted that the mean duration from first disease symptom to rheumatologist consultation was 9.2 months, while the mean time to RA diagnosis was 14.2 months [33]. A similar study found that a delay in PsA diagnosis was greater than one year in nearly half of the patients [34]. The majority of patients with RA received treatment prescribed by a rheumatologist but treatment initiation was also found to be delayed (mean duration from first disease symptom of 16.9 months) [33].…”
Section: Discussionsupporting
confidence: 73%
“…For patients with PSO it is interesting that while the majority of patients are not treated systemically, among those that are treated with a biologic more than half received above-label dosing (53.9%). Delayed PsA diagnosis, which was highlighted in a recent report [ 34 ], is likely a contributing factor to patients not receiving treatment.…”
Section: Discussionmentioning
confidence: 99%